Element‐Ligand Cooperativity with p‐Block Elements - Greb, Lutz; Ebner, Fabian; Ginzburg, Yael; Sigmund, Lukas M. (European journal of inorganic chemistry, 2020)
Metal‐ligand cooperativity (MLC) had a tremendous impact on d‐block metal‐mediated bond activation and homogeneous catalysis. Is this concept translatable to the elements of the p‐block? Are there analogies already at hand? In this review, we describe contributions in which a p‐block element (group 13–15) and its ligand (surrounding molecular framework) operate synergistically in a substrate activation or a catalytic cycle. This activity is termed element‐ligand cooperativity (ELC), in correspondence to MLC. After the concepts of p‐block low‐valent states and frustrated Lewis pairs mimicking the ambiphilic reactivity of transition metals, the spatial proximity of nucleophilic and electrophilic reaction sites and a small HOMO‐LUMO gap in a p‐block ELC complex might offer yet another approach. Selected examples shall illustrate common reactivities of ELC, disclose conceptual analogies with d‐block MLC, and outline shortcomings in this field. Element‐ligand cooperativity (ELC) is an increasingly utilized tool in p‐block element chemistry for bond activation reactions and catalysis. This review compiles manifold examples of ELC for elements of groups 13 to 15, addresses the vague borderline between ELC and intramolecular FLP chemistry, and highlights analogies to the parent field of transition metal‐ligand cooperativity.